Neonatal azithromycin administration to prevent infant mortality: study protocol for a randomised controlled trial. Issue 9 (4th September 2019) - Sie, Ali; Bountogo, Mamadou; Nebie, Eric; Ouattara, Mamadou; Coulibaly, Boubacar; Bagagnan, Cheik; Zabre, Pascal; Lebas, Elodie; Brogdon, Jessica; Godwin, William W; Lin, Ying; Porco, Travis; et al.
Abstract : Introduction: Biannual mass azithromycin distribution to children aged 1–59 months has been shown to reduce all-cause mortality. Children under 28 days of age were not treated in studies evaluating mass azithromycin distribution for child mortality due to concerns related to infantile hypertrophic pyloric stenosis (IHPS). Here, we report the design of a randomised controlled trial to evaluate the efficacy and safety of administration of a single dose of oral azithromycin during the neonatal period. Methods and analysis: The Nouveaux-nés et Azithromycine: une Innovation dans le Traitement des Enfants (NAITRE) study is a double-masked randomised placebo-controlled trial designed to evaluate the efficacy of a single dose of azithromycin (20 mg/kg) for the prevention of child mortality. Newborns (n=21 712) aged 8–27 days weighing at least 2500 g are 1:1 randomised to a single, directly observed, oral dose of azithromycin or matching placebo. Participants are followed weekly for 3 weeks after treatment to screen for adverse events, including IHPS. The primary outcome is all-cause mortality at the 6-month study visit. Ethics and dissemination: This study was approved by the Institutional Review Boards at the University of California, San Francisco in San Francisco, USA (Protocol #18-25027) and the Comité National d'Ethique pour la Recherche in Ouagadougou, Burkina Faso (Protocol #2018-10-123). The findings of this trial will be presented at local, regional and international meetings and published in open access peer-reviewed journals. Trial registration number: NCT03682653 ; Pre-results.